A highly specific and sensitive loop-mediated isothermal amplification method for the detection of Escherichia coli O157:H7. (February 2016) - Ravan, Hadi; Amandadi, Mojdeh; Sanadgol, Nima
Abstract: E. coli O157:H7 is one of the most important foodborne pathogen that causes some human illnesses such as bloody diarrhea, hemolytic-uremic syndrome, and kidney failure. We developed a loop-mediated isothermal amplification (LAMP) assay with six special primers that target a highly specific 299-bp region of the Z3276 gene for the detection of E. coli O157:H7. Among 117 bacterial strains tested in this study, positive results were only obtained from E. coli O157:H7 strains. The sensitivity level of the Z3276-LAMP assay was determined to be 5 CFU/reaction tube in pure bacterial culture. Moreover, the LAMP assay was successfully applied to artificially contaminated ground beef with a sensitivity level of 10 3 CFU/mL without pre-enrichment and 10 CFU/mL after a 4-h pre-enrichment. In conclusion, the present LAMP assay would be a useful and powerful tool for the rapid, sensitive, and specific diagnosis of E. coli O157:H7 strains in resource limited laboratories. Highlights: Detecting of Escherichia coli O157:H7. A highly sensitive and specific LAMP assay for detecting E. coli O157:H7. The LAMP assay can be used for the detection of E. coli O157:H7 in food staffs.